Aperfeiçoamento e especialização: o esperado e o alcançado na visão dos alunos que frequentaram os cursos da Escola Superior de Magistratura do Ceará, nos anos de 1995 a 2002 - Leite, Raimundo Helio (2004)
The object of this thesis was to evaluate, from the point of view of Edmund Husserl's phenomenology, updating and specialization courses for magistrates, given by the Magistry School of Ceará (ESMEC), in the period 1995-2002, through a mutual agreement with the Federal U niversity of Ceará. The universe comprised 522 students. An intentional sample of 60 participants was made in proportion to the size of the each course. This sample represented 11.49 % of the universe. Semi-structured interviews were arranged and recorded in an effort to collect the necessary data. Some secondary sources were also used. Edmund Husserl' s phenomenology (1859-1938) served as a theoretical and methodological support for the analysis. The study presents new insights into Husserl's phenomenology as well as its development in using in using scientific research to offer a more profound philosophical understanding. The Brazilian legal educational system is amply discussed to indicate the absolute necessity of preparatory courses for magistrates and the creation of Magistry Schools. The study, furthermore, offers a comprehensive view of the continual educational programs in the legal field in Brazil as well as in some foreign countries. The data collected offered precise descriptions for the reasons the students had for attending courses, as well as the assessment methodology used by the teachers, and the relationship between theory and practice, together with a variety of suggestions for ESMEC concerning course improvement at the Magistry Scholl of Ceará. The data analysis was carried out in three phases: an empirical description, an eidetic reduction and a transcendental reduction. The empirical description is the normal description made in natural sciences. The second step of the Husserl's method (epoqué) - the eidetic description- identifies certain elements common to the courses. The transcendental reduction, based on the final reduction of teleology and Sinderesys, indicates magistrate quiddity which formed the essence for the phenomenon examined in this thesis.The general conclusions were drawn to support: a) the discovery of the magistrate quiddity, according to the interviewees' personal visions and not of the ones offered in literature; b) The formation of a group capable of making critical judgments and offering sound suggestions regarding the assessment of the courses from an axiological point of view. This type of assessment appears not to have a precedent in assessment literature as it takes in the epistemological connections in the light of Edmund Husserl's thought, as well as the three areas involved in the research: Philosophy, Law and Education. By way of conclusion, quite a few practical suggestions are offered to improve the programs for continuous education at the Magistracy School of Ceará.